2007
DOI: 10.2337/dc06-1814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isoflavone Dietary Supplementation on Cardiovascular Risk Factors in Type 2 Diabetes

Abstract: A diet supplemented with soy protein and isoflavones has been shown to reduce cardiovascular risk factors in postmenopausal women with type 2 diabetes. However, it remains unclear which component is responsible for these effects. Our aim was to determine whether the addition of isoflavones alone modifies cardiovascular disease risk markers in this group of patients. Cardiovascular disease (CVD) is the leading cause of mortality in women in developed countries (1), and women with diabetes are four times more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
54
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 20 publications
11
54
1
1
Order By: Relevance
“…(25) A recent meta-analysis suggested that soy isoflavones significantly reduced total cholesterol and LDL-C but do not change HDL-C. (27) These differences may be attributed to the basal lipid profile or different study designs and isoflavones composition with glucoside instead of aglycone forms. There was a significant reduction in systolic blood pressure within 6 months of SPI supplementation but no change with SP supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(25) A recent meta-analysis suggested that soy isoflavones significantly reduced total cholesterol and LDL-C but do not change HDL-C. (27) These differences may be attributed to the basal lipid profile or different study designs and isoflavones composition with glucoside instead of aglycone forms. There was a significant reduction in systolic blood pressure within 6 months of SPI supplementation but no change with SP supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…(32) These data suggests that a synergistic matrix of soy protein and isoflavones is needed to maximize the effects rather than either soy protein or isoflavone alone. (25,33) In the current study, where all patients had normal thyroid function tests at baseline, none of the patients developed subclinical or overt hypothyroidism. There was also no significant change in fT3 with either SPI or SP supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas some investigators have reported neutral effects of soy on serum lipids 36,37 , beneficial effects have been reported by others 35,[38][39][40] . Recently, favorable effects of soy supplementation on metabolic control in diabetes were reported by Jaygopal and colleagues 41,42 . Thus, despite the neutral effects of soy observed in this study, the possibility of cardioprotective effects, at least in certain population subgroups, still exists.…”
Section: Discussionmentioning
confidence: 95%
“…A meta-analysis of randomised controlled trials (RCTs) (Taku et al, 2008), which assessed the effects of consumption of extracted soy isoflavones vs. placebo on blood LDL-cholesterol concentrations, included the individual studies of this type which were provided in the consolidated list (Cheng et al, 2007;Gonzalez et al, 2007) except three Lissin et al, 2004;Nahas et al, 2007).…”
Section: Maintenance Of Normal Blood Ldl-cholesterol Concentrations (mentioning
confidence: 99%